Pelaksanaan Pembebasan Hak Atas Tanah Harta Pusaka pada Pembangunan Jalan Tol Sesi Padang-Sicincin - Aulianti, Yeyen; Ismi, Hayatul; S, Hengki Firmanda (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study discusses land acquisition in the construction of the toll road regarding the implementation of the release of inheritance land rights in the construction of the Padang-Sicincin toll road. Based on these problems, there are many things that need to be studied because they are not in accordance with the provisions of existing laws and regulations. Therefore, it is necessary to study the first, the Implementation of Exemption of Right to Heritage Land in the Construction of the Sesi Padang-Sicincin Toll Road. Second, the inhibiting factors for the implementation of the waiver of inheritance rights over land in the construction of the Sesi Padang-Sicincin toll road.This research is a sociological juridical legal research. With the research location being located in Padang Pariaman Regency, especially Nagari Kasang, while the population and sample are all parties related to the problem under study. This study uses data sources in the form of primary data and secondary data, and data collection techniques are carried out by means of interviews.From the results of the study, it was concluded that, first, the implementation of the liberation of inheritance land rights in the construction of the padang-sicincin toll road was carried out in accordance with Law Number 2 of 2012 concerning Land Acquisition for Development for Public Interest and Regional Regulation of West Sumatra Province Number 16 of 2008 concerning Ulayat Land and Its Utilization. Second, the inhibiting factors are clan members, the unclear status of land acquisition objects, factors from the government and factors from customary density. The government should pay more attention to and protect the rights and existence of inherited land so that indigenous peoples do not feel they have lost the identity of their customary land. Keywords: Exemption - Land Rights - Inheritance